Compression between Combined Anti-VGEF with Steroids Versus Pure Anti-VEGF in Retinal Vein Occlusion - Abo Taleb Eman; Alsowaidi Altaf (Journal of Ophthalmic Science, 2020)
Aim To compare the efficacy of combined anti-VGEF (IVB) with steroids versus pure anti-VEGF for the treatment of macular edema secondary to retinal vein occlusion (RVO). Methods In this prospective study, 51 eyes were randomized into 2 groups according to treatment of clinically identified macular edema secondary to retinal vein occlusion within 4 weeks of onset: Group 1 (19 eyes) was given intravitreal Bevacizumab (IVB) (1.25mg/.05ml) + Triamcinolone (IVTA) (2mg/.05ml); Group 2 (22 eyes) was given pure intravitreal Bevacizumab (IVB) (1.25mg/.05ml) at baseline, at month 1, and at month 2. The outcome of the study represented the EDRTS letters gain, IOP change and (CRT) by using Spectral domain optical coherence tomography (OCT) at month 1, 2, 3 and 6 in each group. Both central retinal vein occlusion (CRVO) and branch retinal vein occlusion (BRVO) patients with at least 6 months FU were enrolled in the study. Results EDRTS letters gain was (20.37±15.28, 28.05±16.68, 35.16±17.12, 36.47±18.17) in group1 and (14.50±14.56, 18.41±14.56, 20.59±16.13, 21.06±15.72) in group2 at month 2,3 and 6 p value (0.18, .04, 0.004, 0.002). Mean IOP pre-injection (14.00±2.67) in group 1 and (13.5±5.89) in group 2. Group 1 has transient increase in IOP at month 1 and then return to baseline over 6 months. CRT from baseline to final FU decrease by 264.82 (µm) ±147.66 in group 1 and 308.42(µm) ±226.78 in group 2 with no significant difference between two group p value 0.57. There was no significant difference in EDRTS letters gain between CRVO patients and BRVO patients at month 1, 2, 3 and 6 p values (0.83, 0.23, 0.29, 0.13). Conclusion Early treatment macular edema in RVO patients by combined anti-VGEF+ steroid effectively improve functional outcome better than pure anti-VGEF injection.
Keywords: Retinal vein occlusion